Enterprise Surveys : Suriname Country Profile 2010 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The country profile for Suriname is based on data from the enterprise surveys conducted by the World Bank. The enterprise surveys collect a wide array of qualitative and quantitative information through face to face interviews with firm managers and owners regarding the business environment in their countries and the productivity of their firms. The topics covered include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business. The benchmarks include the averages for the group of countries in Latin America and Caribbean and the Suriname income group. Breakdowns by firm size are presented in the appendix along with all indicators used to make the graphs.